Upper limits on atmospheric abundances of KELT-11b and WASP-69b from a retrieval approach - Lesjak, Fabio Robin; Nortmann, L.; Cont, D.; Amado, P. J.; Azzaro, M.; Caballero, J. A.; Czesla, S.; Hatzes, A.; Henning, Thomas; López-Puertas, M.; Molaverdikhani, K.; Montes, D.; et al. (Astronomy and astrophysics, 2025)
Context. WASP-69 b and KELT-11 b are two low-density hot Jupiters, which are expected to show strong atmospheric features in their transmission spectra. Such features offer valuable insights into the chemical composition, thermal structure, and cloud properties of exoplanet atmospheres. High-resolution spectroscopic observations can be used to study the line-forming regions in exoplanet atmospheres and potentially detect signals despite the presence of clouds. Aims. We aimed to detect various molecular species and constrain the chemical abundances and cloud deck pressures using high-resolution spectroscopy. Methods. We observed multiple transits of these planets with CARMENES and applied the cross-correlation method to detect atmospheric signatures. Further, we used an injection-recovery approach and retrievals to place constraints on the atmospheric properties. Results. We detected a tentative H2O signal for KELT-11 b but not for WASP-69 b, and searches for other molecules such as H2S and CH4 resulted in non-detections for both planets. By investigating the signal strength of injected synthetic models, we constrained which atmospheric abundances and cloud deck pressures are consistent with our cross-correlation results. In addition, we show that a retrieval-based approach leads to similar constraints of these parameters.
Online veröffentlicht: 12. Dezember 2025
Gesehen am 20.02.2026